Pengaruh Latihan Ladder Driil terhadap Peningkatan Kemampuan Tendangan Mae Geri pada Atlet Kata FORKI Ogan Ilir - Muhammad Adil; Farizal Imansyah; Puput Sekar Sari (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
The problem addressed in this study is the suboptimal mae geri kicking ability of kata athletes at FORKI Ogan Ilir, which affects their overall technical performance during training and competition. Effective kicking techniques require not only strength but also speed, agility, coordination, and balance. Therefore, an appropriate training method is needed to improve athletes' performance. This study aims to determine whether ladder drill training has a significant effect on improving the mae geri kicking ability of kata athletes at FORKI Ogan Ilir. The research employed a quantitative experimental approach using a One-Group Pre-test Post-test design. The subjects consisted of 15 male and female kata athletes from FORKI Ogan Ilir who participated in the training program. Data were collected through mae geri kicking ability tests administered before and after the training intervention. The data analysis techniques included the normality test, homogeneity test, and paired sample t-test. The results showed that the significance value obtained from the paired sample t-test was 0.000, which was lower than 0.05. These findings indicate that the hypothesis was accepted, demonstrating that ladder drill training had a significant positive effect on improving the mae geri kicking ability of kata athletes at FORKI Ogan Ilir and can be recommended as an effective training method for karate athletes.